Glycosylation Profile of the Transferrin Receptor in Gestational Iron Deficiency and Early-Onset Severe Preeclampsia - Alejandra María Gómez-Gutiérrez; Beatriz Elena Parra-Sosa; Julio Cesar Bueno-Sánchez (Journal of Pregnancy)
Objective. To examine the expression of hypoxia-inducible factor-1α (HIF-1α), TfR1, and TfR1-attached terminal monosaccharides in placentas of women with IDAP and severe preeclampsia. Methods. TfR1 and HIF-1α were detected by western blot. Immunoadsorption of TfR1 was performed to characterize the terminal monosaccharides by specific lectin binding. Results. There was no difference in the expression of TfR1 and HIF-1α between groups. Lectin blot analysis pointed out an overexpression of galactose β1-4 N-acetylglucosamine (Gal-GlcNAc) and mannose in severe preeclampsia. Conclusion. The increase in Gal-GlcNAc may be due to the increased presence of antennary structures and the mannose glycans of TfR1 may indicate the presence of misfolded or incomplete proteins. These findings may be associated with the low expression of placental TfR1 in women with preeclampsia.